Variation of Handedness and Creativity in Bogor Primary and Secondary School Students - Winati Nurhayu; Permesyawari Muktiono; Kanthi Arum Widayati; Bambang Suryobroto (HAYATI Journal of Biosciences, 2023)
Left-handed individual’s minority has been ubiquitous in human population which leads them to be adaptable in right-handed world. As a preference, daily hand used must be consistentacross individuals and tasks, known as handedness. Handedness needs to be assessed with specific tasks using tools due to consistency of using either hand. There is a different adaptation that leads to creativity in left-handed individuals. The aim of this study is to assess left-handed individuals and measure their creativity. Handedness was examined by self-declared and 10 specific tasks of 493 both primary and secondary school students in Bogor, Indonesia. The total frequency of left-handed individuals was 7.3%. It seems that there are special adaptations that may signal creative behavior for left-handed individuals. The result showed that the left-handed females had higher creativity score than the males on Adjective Check List. Age and sex influence on creativity are discussed.